A 60W Tm:YLF Laser with Triple Tm:YLF Rods. (September 2015) - Zhu 朱, Guo-Li 国利
Abstract : A narrow linewidth stable high-power continuous-wave 3.5% Tm 3+ doped LiYF4 (Tm:YLF) laser is reported. By using dual F–P etalons and three Tm:YLF rods in a cavity, laser output of ∼60 W at 1907.7 nm is obtained with a slope efficiency of 34.8%. The M 2 factor is found to be ∼2.0 under an output power of 30 W. In addition, the relaxation oscillation and efficiency of the Tm:YLF laser are also studied. The relaxation oscillation of the Tm:YLF laser is improved obviously by setting the ratio of pump beam to oscillating laser beam as ∼1.5:1 and the efficiency is increased in comparison with the ratio of ∼1.3:1.